Comparison of physical performance characteristics of female and male ice hockey players - Bracko, M. R.; Fellingham, G. W. (Pediatric Exercise Science, 2001)
Fifty-four female and 77 male hockey players ranging in age from 10-15 years volunteered for this study. Demographic data included: age (AGE) and years of playing experience (YPE). Off-ice tests included: height (HGT), body mass (BM), lean body mass (LBM), predicted body fat % (FAT%), 40-yard dash (40YD), vertical jump (VJ), push-ups/min (PUPS), sit-ups/min (SUPS), and sit-and-reach flexibility (S&R). On-ice performance skating tests included: acceleration (ACC), agility (AGL), and speed (SPD). On-ice anaerobic power (AnPow) was calculated using the formula of Watson and Sargeant (18). Generally speaking, the females and males in this study had similar results in off-ice fitness. The males consistently out-performed the females in the on-ice tests. It would be difficult for females to compete with or against same-aged males based on the fact that males are superior skaters. Fifty-four female and 77 male hockey players ranging in age from 10-15 years volunteered for this study. Demographic data included: age (AGE) and years of playing experience (YPE). Off-ice tests included: height (HGT), body mass (BM), lean body mass (LBM), predicted body fat % (FAT%), 40-yard dash (40YD), vertical jump (VJ), push-ups/min (PUPS), sit-ups/min (SUPS), and sit-and-reach flexibility (S&R). On-ice performance skating tests included: acceleration (ACC), agility (AGL), and speed (SPD). On-ice anaerobic power (AnPow) was calculated using the formula of Watson and Sargeant (18). Generally speaking, the females and males in this study had similar results in off-ice fitness. The males consistently out-performed the females in the on-ice tests. It would be difficult for females to compete with or against same-aged males based on the fact that males are superior skaters.